Potentials of artificial intelligence in digital marketing and financial technology for small and medium enterprises - Enshassi, Mohammed; Nathan, Robert Jeyakumar; Soekmawati, Soekmawati; Al-Mulali, Usama; Ismail, Hishamuddin (Institute of Advanced Engineering and Science, 2024)
Small and medium enterprises small and medium enterprises (SMEs) play a crucial role in nations’ economy, through job creations, reducing unemployment rate as well as increase the overall productivity and gross domestic product (GDP) of a country. However, most SMEs are often lagging in technology adoption which could be a game changer for their success. SMEs could adopt new technologies to improve their business operations and profitability. They are also useful in supporting SMEs to penetrate international market. This research suggests that implementation of the artificial intelligence (AI) through digital marketing (DM) and financial technology (Fintech) would assist SMEs to be competitive, current in leveraging on technology and increase their overall profitability. Based on secondary data analysis, this paper presents a conceptual framework of determining factors in adoption of AI through digital marketing and Fintech. It contributes to the academic knowledge of AI, DM and Fintech for small businesses, and presents a testable framework that can be replicated and adapted for future empirical study.